A new diagnostic for multiple populations: NGC 6388 as a test case. Issue Volume 14:Issue S351(2019) (May 2019) - Bragaglia, Angela; Carretta, Eugenio
Abstract: Recently, the sample size of stars with detailed, homogeneous abundances in the massive bulge Globular cluster NGC 6388 expanded to 185 giants. We use this wealth of data to present first results on its multiple stellar populations. In particular, i) we introduce a new diagnostic plot to survey the occurrence of very high temperature for H-burning in the first-generation polluters, and ii) we pinpoint a restricted temperature range reached by polluters at work in NGC 6388.